Cover Feature: Ionic Polyimide Derived Porous Carbon Nanosheets as High‐Efficiency Oxygen Reduction Catalysts for Zn–Air Batteries (Chem. Eur. J. 29/2020). Issue 29 (23rd April 2020) - Tu, Kejun; Zou, Lingyi; Yang, Chongqing; Su, Yuezeng; Lu, Chenbao; Zhu, Jinhui; Zhang, Fan; Ke, Changchun; Zhuang, Xiaodong
Abstract : Two‐dimensional porous carbon nanosheets (2DPCs) with controlled hexagonal morphology are reported, using LDH and ionic polyimide as template and carbon precursor, respectively. Looking at the top right‐hand corner, we can see the polyimide model, which represents the viologen‐linked ionic polyimide with both sp 2 ‐ and sp 3 ‐hybridized nitrogen atoms. Such an ionic polyimide acts as the carbon precursor for 2DPCs. Looking at the bottom left corner, we can see an oxygen molecule, with electrons on a sharp arrow pointing the way to a lighting bulb, suggesting the typical oxygen reduction reaction (ORR) with four‐electron mechanism and production of electricity for typical Zn‐air batteries. This cover highlights that 2DPCs with large lateral sizes can provide long‐distance conductivity and connected heteroatom active sites to boost the performance for energy conversion and storage. More information can be found in the Full Paper by Y. Su, F. Zhang, C. Ke, X. Zhuang, et al. on page 6525 .